Penguatan Tata Kelola Capacity Building Dalam Mitigasi Pekerja Migran Indonesia di Perbatasan Entikong Kalimantan Barat - Alunaza, Hardi; Putri, Anggi; Ernianda, Annisa (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2024)
This study aims to determine the governance of State Cross Border Posts in the field of capacity building and governance through border diplomacy during the handling of Covid-19 at the Entikong border in West Kalimantan. This study uses a qualitative approach with a descriptive study method within the framework of border governance theory and the concept of vitalization function. Data collection techniques used interviews and literature study. The data sources for this study are the Coordinator of the Entikong Indonesian Migrant Worker Protection Agency, the head of class II immigration, Entikong, West Kalimantan and the Head of Entikong District, as well as staff from the Entikong State Cross Border Post, as well as literature studies that come from reliable sources. Data analysis includes several stages, namely data collection, data simplification, presentation and drawing conclusions. Data validity was carried out using triangulation techniques. The results of this study are that the governance of the Entikong State Cross-Border Post already has fairly good infrastructure, such as the State Cross-Border Post office, International Land Terminal and other infrastructure. Improving governance in the field of capacity building at the Entikong State Cross-Border Post is carried out by increasing cooperation, facilities and in general it can be said that the capacity of the Entikong State Cross-Border Post has, especially when facing the Covid-19 pandemic. Another strategy is border diplomacy or cooperation between Indonesia and Malaysia.